2022
DOI: 10.1002/pen.26009
|View full text |Cite
|
Sign up to set email alerts
|

New cross‐linked poly(methyl methacrylate): Synthesis, characterization, and inhibitory effects against selected bacteria and cancer cells

Abstract: Novel cross-linked poly(methyl methacrylate) (PMMA) derivatives with different ratios of crosslinkers (2, 5, 10, 20, 30, 40, and 50 wt%) were synthesized using the condensation method between PMMA and bifunctional amino derivative cross-linkers, o-phenylenediamine (OPD), and m-phenylenediamine (MPD). The final products were tested for antibacterial and anticancer activities. Various techniques were used to characterize the cross-linked polymers. Fourier transform infrared (FTIR) spectroscopy was used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…O-Phenylenediamine (OPD), known as 1,2-phenylenediamine, is often used as an intermediate in the preparation of photographic materials, pharmaceuticals, dyes and rubber antioxidants due to its good radical-capturing activity. [14][15][16][17][18] It has been reported that the chemical grafting of OPD onto graphene oxide, the hydroxyl group of graphene oxide can react with the amino group of OPD to generate new quinone and phenazine structures, which improve the mechanical properties and aging resistance of NBR composite. [19] However, graphene oxide is costly and not conducive to widespread applications.…”
Section: Introductionmentioning
confidence: 99%
“…O-Phenylenediamine (OPD), known as 1,2-phenylenediamine, is often used as an intermediate in the preparation of photographic materials, pharmaceuticals, dyes and rubber antioxidants due to its good radical-capturing activity. [14][15][16][17][18] It has been reported that the chemical grafting of OPD onto graphene oxide, the hydroxyl group of graphene oxide can react with the amino group of OPD to generate new quinone and phenazine structures, which improve the mechanical properties and aging resistance of NBR composite. [19] However, graphene oxide is costly and not conducive to widespread applications.…”
Section: Introductionmentioning
confidence: 99%